Negative electrode of solid-state battery and solid-state battery

The negative electrode design for solid-state batteries, featuring a metallic porous body current collector with strategically placed hole portions, addresses the challenge of metallic lithium deposition, enhancing battery life and energy efficiency.

JP2025057053AActive Publication Date: 2025-04-09HONDA MOTOR CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023166682
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Solid-state batteries face challenges in maintaining battery life and energy efficiency due to the deposition of metallic lithium, which can lead to internal short circuits and decreased capacity during repeated charge and discharge cycles.

Method used

A negative electrode with a metallic porous body current collector featuring hole portions without metallic porous bodies, specifically designed to concentrate metallic lithium deposition within these holes, thereby reducing the risk of internal short circuits and maintaining high energy density.

Benefits of technology

The proposed negative electrode design effectively suppresses the deposition of metallic lithium on the electrode interface, thereby enhancing battery life and energy efficiency, even with higher loading densities of electrode active material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025057053000001_ABST
    Figure 2025057053000001_ABST
Patent Text Reader

Abstract

To provide a negative electrode of a solid-state battery, in which an inner short circuit or the like due to deposition of a metal lithium hardly occurs even in the case where a charging and a discharging are repeated while having a large filling of an electrode active material, and contribute to an energy efficiency of the further solid-state battery by providing the negative electrode of the solid-state battery.SOLUTION: A negative electrode of a solid-state battery comprises: a negative electrode collector having a metal porous body as a construction material; and a negative electrode active material filled with the negative electrode collector. In the negative electrode collector, a hole part without the metal porous body is provided in a thickness direction from a front surface on the solid-state battery. A hole diameter of the hole part is 100 μm to 180 μm, and a depth in the thickness direction is larger than the hole diameter.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a solid-state battery and a solid-state battery. [Background technology]

[0002] In recent years, research and development of solid-state batteries that contribute to energy efficiency has been conducted to ensure that more people have access to affordable, reliable, sustainable and advanced energy. Solid-state batteries have high energy density and are used in a wide range of applications. In particular, lithium-ion secondary batteries, which can be rapidly charged and discharged, are important as a sustainable and advanced energy source and are also used as a power source for electric vehicles (EVs) and hybrid electric vehicles (HEVs).

[0003] As a configuration of a solid-state battery, a configuration in which a current collector constituting a negative electrode is made of foam metal in order to increase the packing density of the electrode active material is known. Patent Document 1 discloses a semi-solid battery in which a porous coating layer is arranged on an electrode layer as a semi-solid battery using foam metal as a current collector. The porous coating layer in Patent Document 1 can absorb and trap the electrolyte extruded from the electrode layer even when the negative electrode active material expands during charging of the semi-solid battery, and can suppress the decrease in electrolyte and the decrease in capacity due to repeated charging and discharging. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 7008737 specification Summary of the Invention [Problem to be solved by the invention]

[0005] In order to contribute to further energy efficiency, it is also required that the solid-state battery can maintain its battery life even when it is repeatedly charged and discharged. For example, the required characteristics for this purpose include the control of lithium ions, sodium ions, etc. receiving electrons at the negative electrode and the deposition of metallic lithium, metallic sodium, etc. on the negative electrode when the solid-state battery is repeatedly charged and discharged. When metallic lithium, etc. is deposited on the negative electrode, gaps are likely to be formed between the layers, which may increase the resistance of the solid-state battery, and an internal short circuit may occur in which the positive electrode and the negative electrode are electrically contacted. In particular, the deposition of metallic lithium, etc. is likely to occur in a high-capacity negative electrode.

[0006] In light of this background, the present invention provides an anode that, when used in a solid-state battery, has a packing density of an electrode active material of a predetermined level or more and is less susceptible to the effects of precipitation of metallic lithium, etc., such as internal short circuits, etc. The provision of such an anode for a solid-state battery contributes to further improving the energy efficiency of solid-state batteries. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention provides the following means. [1] A negative electrode of a solid-state battery, comprising: a negative electrode current collector made of a metal porous body as a constituent material; and a negative electrode active material filled in the negative electrode current collector, wherein the negative electrode current collector has pores that are free of the metal porous body from the surface on the solid electrolyte side in a thickness direction, and the pores have a pore diameter of 100 μm to 180 μm.

[0008] In the case where the precipitation of metallic lithium or the like occurs in the negative electrode, the precipitation of metallic lithium or the like tends to occur intensively inside the pores, and the precipitation of metallic lithium or the like at the negative electrode interface or the like is easily suppressed. Therefore, when the negative electrode of [1] is used as a solid-state battery, the amount of negative electrode active material per unit area of ​​the negative electrode is set to a predetermined amount or more, and the battery life is not easily reduced even when the negative electrode is repeatedly charged and discharged.

[0009] [2] The negative electrode of the solid-state battery according to [1], wherein a ratio of a total volume of the pores to a porosity of the metal porous body (total pore volume / porosity) is 10 vol% or less.

[0010] A negative electrode having a total volume ratio of the pores within the above range is likely to maintain a high energy density as a solid-state battery. If the total volume ratio of the pores is too large, it is difficult to maintain a high amount of negative electrode active material, and the energy density tends to decrease. This is because the capacity of the pores becomes excessively larger than the volume of metallic lithium etc. deposited during charging, making it difficult to maintain a high energy density due to the negative electrode active material filling the metal porous body.

[0011] [3] The negative electrode of the solid-state battery according to [1] or [2], wherein a ratio of the total volume of the pores to the porosity of the metal porous body (total pore volume / porosity) is 8 vol% or less.

[0012] [3] A solid-state battery having a negative electrode can easily maintain a high energy density. As shown in Fig. 3 described later, according to the present inventors, when the ratio of the total pore volume to the porosity is 8 vol% or less, the decrease in energy density can be more reliably suppressed.

[0013] [4] The negative electrode of the solid state battery according to any one of [1] to [3], wherein the pores have a depth in the thickness direction of 3 μm or more.

[0014] When the holes have a depth equal to or greater than the above-mentioned range, there tends to be a sufficient space for deposition when metallic lithium or the like is deposited during charging, which tends to result in a solid-state battery with a high energy density.

[0015] [5] The negative electrode of the solid-state battery according to any one of [1] to [4], wherein the pores have a depth in the thickness direction of 5 μm or more.

[0016] When the holes have a depth equal to or greater than the above-mentioned range, there tends to be more reliable space for lithium or the like to be deposited when metallic lithium or the like is deposited during charging, which tends to result in a solid-state battery with even higher energy density.

[0017] [6] The negative electrode for the solid-state battery according to any one of [1] to [5], wherein the hole is a through hole.

[0018] When the pores are through-holes, lithium ions and the like tend to be uniformly supplied to the pores, metallic lithium and the like tend to deposit stably in the pores, and cycle characteristics tend to be more easily maintained.

[0019] [7] The negative electrode of the solid-state battery according to any one of [1] to [6], wherein the hole has a circular or rectangular cross-sectional shape.

[0020] When the cross-sectional shape of the hole is circular, metallic lithium or the like can be stably precipitated in the hole. When the cross-sectional shape of the hole is rectangular, the specific surface area per volume of the hole is large. Therefore, for example, during rapid charging, initial precipitation of metallic lithium or the like can be stably formed in the hole.

[0021] [8] The negative electrode of the solid-state battery according to any one of [1] to [7], wherein the negative electrode active material is a silicon-based material.

[0022] The above-mentioned negative electrode is suitably used when the negative electrode active material is a silicon-based material.

[0023] [9] A solid-state battery comprising a negative electrode according to any one of [1] to [8]. Effect of the Invention

[0024] According to a solid-state battery including the above-described negative electrode, the packing density of the electrode active material can be set to a predetermined level or higher, and a decrease in battery life due to precipitation of metallic lithium or the like can be suppressed. [Brief description of the drawings]

[0025] [Figure 1] FIG. 2 is a conceptual diagram showing a negative electrode and a solid electrolyte of a solid-state battery according to the present embodiment. [Diagram 2] FIG. 2 is an enlarged conceptual diagram of a part of FIG. 1 regarding the negative electrode in the present embodiment. [Diagram 3]FIG. 1 is a graph showing the value of energy density versus the capacity of a negative electrode active material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Preferred embodiments of the present invention will now be described in detail.

[0027] [Anode of solid-state battery] The negative electrode of the solid-state battery of this embodiment includes a negative electrode current collector made of a porous metal material and a negative electrode active material filled in the negative electrode current collector. The negative electrode current collector has holes that are free of a porous metal material from the surface on the solid electrolyte side in the thickness direction, and the holes have a hole diameter of 100 μm to 180 μm.

[0028] The negative electrode of this embodiment is used in a solid-state battery having a structure in which a solid electrolyte is filled between a positive electrode and a negative electrode. Solid-state batteries are known to have the advantages of low risk of fire, rapid charging, and long life with little deterioration. The structure of the solid-state battery is not particularly limited, and may be any configuration such as a cylindrical or angular wound type, a laminated layered type, or the like.

[0029] The negative electrode of the present embodiment is unlikely to cause a decrease in battery life due to repeated charging and discharging even when used in a solid-state battery. In this respect, a short circuit phenomenon caused by deposition of metallic lithium or the like on the negative electrode is more likely to occur in a solid-state battery than in a secondary battery in which the electrolyte is liquid, for the following reasons. In contrast, the negative electrode of the present embodiment is likely to suppress deposition of metallic lithium or the like on the negative electrode interface, etc., so that the battery life is unlikely to decrease even in a solid-state battery.

[0030] In solid-state batteries, the occurrence of a short circuit phenomenon when metallic lithium or the like is precipitated at the negative electrode interface or the like is believed to be caused by the following reasons. In solid-state batteries, the negative electrode and the solid electrolyte layer form an interface between the solids. When metallic lithium is precipitated, lithium ions are less likely to be conducted at the interface between the negative electrode and the solid electrolyte at the precipitation site, and the resistance is also likely to increase. This makes it easier for cracks to occur in the electrode or solid electrolyte layer, making it difficult for the cell to function, and the precipitated metallic lithium is more likely to penetrate into the gaps in the solid electrolyte layer, causing a short circuit phenomenon. On the other hand, in secondary batteries with a liquid electrolyte, even if a crack occurs in the electrode, the liquid electrolyte penetrates into the crack and the conduction of lithium ions, etc. is maintained. Even if metallic lithium, etc., precipitates between the electrode and the separator, a short circuit does not occur until the separator breaks, so the time until a short circuit occurs is longer than in solid-state batteries.

[0031] In addition, the solid-state battery having the negative electrode of this embodiment is preferably used in a lithium-ion secondary battery having a positive electrode, a negative electrode, a solid electrolyte, and other battery elements as necessary. The lithium-ion secondary battery can be applied to a wide range of applications, such as mobile devices such as mobile phones and notebook computers, and vehicle-mounted applications. The lithium-ion secondary battery only needs to have the configuration of this embodiment as the negative electrode. The configuration other than the negative electrode may be the battery element of a known lithium-ion secondary battery as it is. The configuration of the lithium-ion secondary battery may be, for example, a lithium-ion secondary battery in which the negative electrode of this embodiment, a positive electrode facing the negative electrode, and a solid electrolyte layer located between the positive electrode and the negative electrode are laminated.

[0032] (Negative electrode current collector) The negative electrode current collector is made of a metal porous body. The metal porous body is not particularly limited as long as it is a metal material having a porous space generated by foaming. The metal constituting the metal porous body may be, for example, nickel, nickel-chromium alloy, aluminum, stainless steel, titanium, copper, silver, etc., and copper or stainless steel is preferable.

[0033] The negative electrode current collector made of a metal porous body has a large surface area. The surface area of ​​the negative electrode current collector is not particularly limited, but is preferably 1000 to 6000 m 2 / m 3 It is preferable that the negative electrode current collector is filled with an electrode mixture containing a negative electrode active material, thereby increasing the amount of active material per unit area of ​​the electrode layer. Therefore, the negative electrode of this embodiment has a high energy density when used as a solid-state battery. In addition, if the negative electrode current collector is a metal porous body, it is easy to form a thick active material layer without thickening the electrode mixture. Therefore, the negative electrode of this embodiment is easy to achieve a high capacity when used as a solid-state battery.

[0034] The negative electrode current collector is assumed to have holes. The holes of the negative electrode current collector will be described with reference to the image diagrams of FIG. 1 and FIG. 2. In FIG. 1, the negative electrode current collector 21 of the negative electrode 1 is filled with a negative electrode active material 23. The negative electrode current collector 21 is provided with holes 22 in the thickness direction W from the surface on the solid electrolyte 31 side. The holes 22 do not have the metal porous body constituting the negative electrode current collector 21, that is, the holes 22 are spaces (voids) that do not have a skeleton of the metal porous body. Note that the holes 22 may have metallic lithium precipitates present inside when used as a solid-state battery.

[0035] The reason why the negative electrode having the negative electrode current collector having the holes has a high energy density as a solid-state battery is as follows. When the battery is repeatedly charged and discharged as a solid-state battery, the lithium ions and electrons present near the negative electrode are likely to be transmitted to the inside of the holes along the metal skeleton and solid electrolyte particles of the negative electrode current collector. These lithium ions are likely to be stably precipitated as metallic lithium inside the holes. In such a solid-state battery, the position of lithium precipitation can be controlled, compared to a conventional solid-state battery in which metallic lithium is precipitated at random positions on the negative electrode. Therefore, the internal short circuit caused by the precipitation of metallic lithium in the conventional solid-state battery is suppressed, resulting in a solid-state battery with high cycle characteristics.

[0036] The pore diameter R is 100 μm to 180 μm, and preferably 120 μm to 180 μm. If the pore diameter R is too small, the number of holes needs to be increased to maintain the space for depositing metallic lithium, and the strength of the negative electrode current collector is likely to decrease. If the pore diameter R is too large, the surface area of ​​the metal porous body is reduced, making it difficult to maintain a high energy density. In addition, the pore diameter R is the diameter (inner diameter) of a circle when the cross-sectional shape (cross-sectional shape) of the hole in the horizontal direction (hereinafter referred to as the "horizontal direction") perpendicular to the thickness direction W is circular, and is the diameter of an inscribed circle when the cross-sectional shape is rectangular. In this embodiment, the pore diameter R refers to an average value calculated from the image of the hole extracted by binarizing an image observed with an electron microscope at a magnification of 50 times from the surface of the negative electrode current collector on the solid electrolyte side.

[0037] The cross-sectional area of ​​the hole 22 in the horizontal direction is 6.0×10 ―5 cm 2 ~3.0×10 ―4 cm 2 If the cross-sectional area is too small, it is difficult for metallic lithium to be appropriately deposited in the holes 22, and if the cross-sectional area is too large, it is difficult to maintain a high energy density as a solid-state battery.

[0038] The depth H of the holes 22 in the thickness direction W is preferably larger than the hole diameter R (see FIG. 2). The depth H is the length from the surface of the negative electrode current collector 21 on the solid electrolyte side to the tip inside the hole 22 (if the hole 22 is a through hole, it is the same as the film thickness of the metal porous body in the thickness direction W). When the depth H of the hole 22 is larger than the hole diameter R, the negative electrode becomes one in which metallic lithium is likely to be stably precipitated inside the hole while ensuring a sufficient filling amount of the negative electrode active material 23. In addition, from the viewpoint of ensuring a sufficient capacity for precipitating metallic lithium inside the hole 22, the depth H of the hole 22 in the thickness direction W is preferably 3 μm or more, and particularly preferably 5 μm or more.

[0039] The number of holes 22 (hole count) provided in the negative electrode current collector is not particularly limited. From the viewpoint of easily securing a sufficient capacity for depositing metallic lithium inside the holes 22, the number of holes is set to 2 (holes / cm) relative to the surface area of ​​the negative electrode current collector 21.2 ) or more, and 5 (pieces / cm 2 From the viewpoint of easily maintaining the strength of the negative electrode current collector, the number of holes is preferably 10 (holes / cm2) or more relative to the surface area of ​​the negative electrode current collector 21. 2 ) or less, and 9 (pieces / cm 2 ) or less is even more preferable.

[0040] As described above, it is preferable that the hole 22 has an internal volume that allows metallic lithium to be sufficiently precipitated. On the other hand, if the internal volume of the hole 22 is excessive, a wasted space in which metallic lithium is not precipitated is retained. In this case, it tends to be difficult for the negative electrode to maintain the amount of the negative electrode active material filled and to maintain a high energy density as a solid-state battery. In this regard, when the negative electrode of this embodiment is used as a solid-state battery, the amount of metallic lithium precipitated on the negative electrode current collector 21 varies depending on the cell configuration, the current value during charging, and the like. In consideration of such fluctuations due to the configuration of the solid-state battery, it is preferable that the hole diameter R of the hole 22 is 2L or less (R≦2L) with respect to the lithium growth rate L (μm / h) when charging at 1C. The negative electrode 1 in which the hole diameter R within the above range is provided on the negative electrode current collector 21 can be a solid-state battery with a high energy density that can handle rapid charging and high output. The lithium growth rate L when charging at 1C is 3mAh / cm 2 at a specified capacity of 1C. 2 The pore size R in this embodiment is preferably determined based on a lithium growth rate L of 50 to 90 μm / h.

[0041] The ratio of the total volume of the holes to the porosity of the metal porous body (total hole volume / porosity) is preferably 10 vol% or less, and particularly preferably 8 vol% or less. The total volume of the holes 22 can be said to be a space provided for the deposition of metallic lithium. For this reason, when the ratio of the total volume of the holes 22 to the porosity of the metal porous body 21 is within the above range, it is easy to maintain a higher energy density as a solid-state battery. Although the lower limit of the ratio is not limited, from the viewpoint of easily securing a space for deposition of metallic lithium, it is preferably 1 vol% or more, and particularly preferably 5 vol% or more. The porosity (air volume) of the negative electrode current collector 21 can be measured by a gas adsorption method or a mercury porosity method. The total hole volume is obtained by multiplying the volume per hole by the number of holes. The volume per hole can be calculated from the depth and cross-sectional area, or the depth, cross-sectional shape, and hole diameter, measured by observing the holes cut horizontally by an argon beam or the like with an electron microscope.

[0042] When the deposition of metallic lithium in the holes 22 proceeds uniformly on the inner surfaces of the holes 22, metallic lithium grows more stably than when the deposition proceeds unevenly depending on the location, and the cycle characteristics of the solid-state battery are more easily maintained. From the viewpoint of uniform deposition of metallic lithium in the holes 22, the holes 22 are preferably through-holes. When the holes 22 are through-holes, lithium ions easily enter the holes 22 uniformly from above and below the holes 22. For this reason, metallic lithium is more likely to deposit uniformly and stably than in holes 22 having a bottom surface.

[0043] Further, the cross-sectional shape of the hole portion 22 (the shape in the horizontal direction when observing the hole portion 22 from the solid electrolyte side) is not particularly limited and may be circular, elliptical, square, polygonal, star-shaped, or the like. The cross-sectional shape of the hole portion 22 is preferably circular or square. When the cross-sectional shape is circular, lithium is likely to be uniformly deposited on the hole portion 22, and it is easy to maintain cycle characteristics as a solid battery. When the cross-sectional shape of the hole portion 22 is square, the specific surface area inside the hole portion 22 can be increased. Therefore, when rapid charging or the like is performed as a solid battery, initial lithium deposition tends to proceed easily. In the case where the cross-sectional shape is elliptical, the pore diameter is the arithmetic mean of the major axis and the minor axis. In the case of a polygon, it is the diameter of the inscribed circle, and in the case of a star shape, it is the diameter of the circumscribed circle.

[0044] (Negative electrode active material) The negative electrode active material 23 is not particularly limited, and known battery elements of solid batteries can be adopted. Examples of the negative electrode active material 23 include silicon-based materials, carbon-based materials, and metal-based materials. The negative electrode 1 of the present embodiment is preferably used when the negative electrode active material 23 is a high-capacity silicon-based material. Here, when a silicon-based material is used as the negative electrode active material 23, silicon is likely to expand and contract when the solid battery is repeatedly charged and discharged. Therefore, the negative electrode active material 23 tends to slide off from the negative electrode current collector 21, the interface becomes unstable, and the precipitation of metallic lithium is likely to be accelerated. On the other hand, the negative electrode 1 of the present embodiment also allows metallic lithium to be stably deposited on the hole portion 22 even when a silicon-based material negative electrode active material 23 is used. Further, since the negative electrode current collector 21 is a metal porous body, the negative electrode active material 23 is less likely to slide off.

[0045] Examples of the silicon-based material for the negative electrode active material 23 include SiOx (0 < x < 2), composites of silicon and carbon such as Si-C. Examples of the carbon-based material may include graphite, carbon nanotubes, non-graphitizable carbon (hard carbon), graphitizable carbon (soft carbon), and low-temperature fired carbon. Examples of the metal-based material include lithium-based materials, aluminum-based materials, silicon-based materials, and tin-based materials.

[0046] The negative electrode active material 23 is applied in an amount of 2 mg / cm 2 relative to the surface area of ​​the negative electrode current collector 21. 2 ~10mg / cm 2 If the amount of the negative electrode active material 23 filled is too small, it tends to be difficult to maintain a high energy density, and if the amount of the negative electrode active material 23 filled is too excessive, it is difficult to contribute to improving the characteristics.

[0047] The negative electrode active material 23 may be filled in the negative electrode assembly 21 as a negative electrode mixture containing a binder. The binder may be a known material, such as a fluororesin-based material. The negative electrode mixture may contain a conductive assistant as necessary.

[0048] [Lithium-ion secondary battery] The negative electrode of the present embodiment is suitable for use in a lithium ion secondary battery including a negative electrode, a positive electrode, a solid electrolyte, and other battery elements as required. The lithium ion secondary battery may employ a known battery element such as a battery container.

[0049] The solid electrolyte is not particularly limited as long as it is a material capable of conducting lithium ions. For example, the solid electrolyte may be a polymer-based solid electrolyte such as a polyethylene oxide-based polymer compound, a polymer compound containing at least one of a polyorganosiloxane chain or a polyoxyalkylene chain, a sulfide-based solid electrolyte, or an oxide-based solid electrolyte.

[0050] The positive electrode may be, for example, a positive electrode current collector having a layer containing a positive electrode active material formed thereon. The positive electrode active material is not particularly limited, and known materials may be applied. Examples of the positive electrode active material include layered positive electrode active material particles, spinel type positive electrode active material, and olivine type positive electrode active material. The layer containing the positive electrode active material may contain a binder, a conductive assistant, a solid electrolyte, and the like. The binder and the conductive assistant are not particularly limited, and known materials for solid-state batteries may be applied.

[0051] [Method of manufacturing the negative electrode] The negative electrode of this embodiment can be manufactured by a manufacturing method including a negative electrode active material filling step of filling a negative electrode current collector made of a metal porous body with a negative electrode active material, and a hole forming step of forming holes in a negative electrode precursor. Other manufacturing steps are not particularly limited, and a known method used as a manufacturing method for a solid-state battery may be applied.

[0052] (Negative electrode active material filling process) The method for filling the negative electrode current collector with the negative electrode active material is not particularly limited, and a known method may be applied. For example, this filling step may be a method of coating the inside of the voids in the negative electrode current collector with a negative electrode mixture containing the negative electrode active material using a die coater or the like. The coating of the negative electrode mixture may be performed by dipping coating, plunger type die coating, comma coating, blade coating, or the like instead of die coating. From the viewpoint of easily maintaining a high energy density, the coating amount of the negative electrode active material on the negative electrode current collector is set to 2 mg / cm. 2 ~10mg / cm 2 The method of the present embodiment may further include a drying step of drying the negative electrode current collector after the step of filling the negative electrode active material. The drying step is preferably performed under conditions of a pressure of 100 to 800 MPa and a drying temperature of 25°C to 120°C.

[0053] (Hole forming process) The hole forming step may be performed by any known method as long as it is a method capable of forming holes having the above-mentioned hole diameter and depth in the negative electrode current collector. The hole forming step may be performed, for example, by a roll press method in which a roll having a predetermined unevenness on its surface is pressed with a predetermined pressure. The shape and depth of the unevenness provided on the roll and the pressing pressure are adjusted to form holes having the hole diameter and depth of the present embodiment. EXAMPLES

[0054] Examples of the present invention will be described below, but the present invention is not limited to the following examples.

[0055] [Example 1] The negative electrode current collector has a thickness of 1 mm, a porosity of 98%, and a specific surface area of ​​5800 m 2 / m 3 A copper foam of 1000 g was prepared.

[0056] A negative electrode mixture was prepared containing silicon (average particle size 5 μm) as the negative electrode active material, acetylene black as the conductive additive, and styrene butadiene rubber (SBR) as the binder. The prepared negative electrode mixture was applied to a substrate with a coating amount of 10 mg / cm. 2 The negative electrode current collector was filled with the mixture using a die coater so that the mixture became as follows: The negative electrode current collector after filling was dried in vacuum at 120° C. for 12 hours.

[0057] Next, the negative electrode current collector was roll-pressed at a pressure of 500 MPa using a conventional roll press machine. 2 The negative electrode current collector was roll-pressed at a pressure of 500 MPa using rolls arranged at intervals. The average hole diameter and the number of holes formed in the negative electrode current collector after roll pressing were counted within a 100x observation field of an electron microscope. The average cross-sectional area of ​​the holes in the horizontal direction was also calculated. The measurement results are shown in Table 1 together with the measurement results of the following Examples and Comparative Examples.

[0058] [Examples 2 to 4] The circular projections on the roll are spaced 4.6 per cm. 2 (Example 2), 4.1 strands / cm 2 (Example 3), 2.6 strands / cm 2 Example 4 A negative electrode having holes formed therein was produced in the same manner as in Example 1, except that a roll was used.

[0059] [Example 5] The pore size in the negative electrode is 100 μm, and the number of pores is 9.2 / cm. 2 Except for this, the same cell design as in Example 1 was carried out. A roll was used in which the circular protrusions arranged on the roll had a diameter of 100 μm.

[0060] [Comparative Example 1] Except for not performing the second roll press on the negative electrode current collector coated with the negative electrode mixture and dried, a negative electrode current collector was produced in the same manner as in Example 1. In the negative electrode current collector of Comparative Example 1, when observed within a 100x visual field of an electron microscope, no visible holes of 500 nm or more could be observed.

[0061] [Comparative Example 2] The same cell design as in Example 1 was carried out, except that the pore diameter in the negative electrode was 200 μm. The diameter of the circular protrusions arranged on the roll was 200 μm, and the interval between the protrusions was 4.7 / cm. 2 A negative electrode having holes formed therein was produced in the same manner as in Example 1, except that a roll having a diameter of 100 mm was used.

[0062] [Comparative Example 3] The same cell design as in Example 1 was carried out, except that the pore diameter in the negative electrode was 80 μm. The diameter of the circular protrusions arranged on the roll was 80 μm, and the interval between the protrusions was 10.8 pieces / cm. 2 A negative electrode having holes formed therein was produced in the same manner as in Example 1, except that a roll having a diameter of 100 mm was used.

[0063] For each of the negative electrodes of the Examples and Comparative Examples prepared above, the processing precision and electrode strength were confirmed by the following measurement methods.

[0064] [Processing accuracy] The prepared negative electrode was cut into 1 cm pieces with an insulating ceramic blade, and then cut horizontally in a vacuum with an argon beam (intensity: 4 kV, irradiation time: 12 hr, temperature: -60) using a cross-section preparation device (JEOL, model number: IB-19530CP) to confirm the processability. The cut cross section was observed with an electron microscope to confirm the horizontal cross-sectional shape of the hole and the depth of the hole. In Examples 1 to 5 and Comparative Example 2, a circular cross-sectional shape was observed. In Comparative Example 3, the metal porous body collapsed during cutting, and the cross-sectional shape after processing could not be confirmed. The holes in Examples 1 to 5 were all through holes. The results of the processability and the cross-sectional shape, cross-sectional area, and depth of the hole are shown in Table 1. In addition, the ratio of the total volume of the hole to the porosity of the negative electrode current collector (total volume of hole / porosity) is shown in Table 1. The total volume of the holes was calculated by multiplying the volume per hole by the number of holes after calculating the volume per hole from the average cross-sectional area and depth. The workability was evaluated according to the following criteria. <Evaluation of processability> ◯: Cutting was performed satisfactorily, and the cross section and shape of the hole after processing could be confirmed. △: The hole was distorted by the argon beam during processing, and the shape of the hole was slightly deformed and could not be clearly confirmed. ×: The porous metal body collapsed during cutting, cutting was not performed well, and the shape of the cross section after processing could not be confirmed.

[0065] [Electrode strength] The negative electrode prepared above was bent using a bending tester (MTI, model number EQ-MBT-12-LD) with a mandrel diameter of 32 mm to check for peeling of the negative electrode active material, etc. The results of the electrode strength evaluated according to the following criteria are shown in Table 1. <Evaluation of electrode strength> ◯: Peeling of the negative electrode active material was not observed. Δ: Partial peeling of the active material was observed. ×: In addition to the peeling of the active material, the electrode structure was destroyed.

[0066] [Preparation of lithium-ion secondary batteries] The positive electrode active material Li(Ni 0.6 Co 0.2 Mn0.2 )O 2 and thio-LISICON (Li 3.25 Ge 0.25 P 0.75S4 ), acetylene black as a conductive additive, styrene-butadiene rubber (SBR) as a binder, and butyl butyrate as a solvent were charged into a planetary centrifugal mixer and stirred at 2000 rpm for 3 minutes, followed by degassing for 1 minute to prepare a positive electrode mixture. The mass ratio of the positive electrode active material, solid electrolyte, conductive additive, and binder was 75:22:3:3. The positive electrode mixture was applied to aluminum foil as a positive electrode current collector and heated at 60°C. After heating, a roll press was performed to obtain a density of 3.1 g / cc and a basis weight of 26 mg / cm. 2 Thus, a positive electrode having a positive electrode mixture layer of this size was obtained.

[0067] Next, we used the solid electrolyte thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S 4 ) was compacted at a compaction pressure of 150 MPa using a zirconium tube with a diameter of 10 mm to obtain a solid electrolyte layer with a diameter of 10 mm. The positive electrode and the solid electrolyte layer with a diameter of 10 mm were compacted at a compaction pressure of 1000 MPa to obtain a laminate of the positive electrode and the solid electrolyte layer (positive electrode-solid electrolyte layer laminate).

[0068] A lithium ion secondary battery was produced by joining the above obtained positive electrode-solid electrolyte layer laminate and the negative electrode of Example 1 at 60 MPa. Lithium ion secondary batteries were also produced by the same production method for the negative electrodes of Examples 2 to 5 and Comparative Examples 1 to 3.

[0069] [Charge / discharge test] The lithium ion secondary battery thus fabricated was subjected to CC charging at a rate of 0.05C up to 4.3V under a temperature condition of 60°C, and then, after a rest period of 10 minutes, a charge-discharge test was performed at a cutoff potential of 2.5V at 0.05C. The charge-discharge test started with charging. Table 1 shows the evaluation of the state of Li deposition and the energy density as the results of the charge-discharge test using the lithium ion secondary batteries of each Example and Comparative Example. The state of Li deposition was evaluated based on the charge-discharge curve according to the following criteria. <Evaluation of Li Precipitation> 〇: No specific variation was confirmed in the charging curve. △: Voltage drop due to micro short - circuit was confirmed in the charging curve, but charging could be carried out. ×: Short - circuit occurred due to abnormal Li precipitation during charging, and sufficient charging could not be achieved.

[0070] [Growth rate of Li when charging at 1C] For each lithium - ion secondary battery of the examples and comparative examples, the growth rate was measured when constant - current charging was carried out at 1C until the specified capacity of 3 mAh / cm 2 was reached. The growth of lithium was measured by microscopic observation to confirm that lithium was deposited in the pores. As a result of the above measurement, for all the examples and comparative examples, the growth thickness of lithium per hour, that is, the growth rate of Li, was 90 μm / h.

[0071] Fig. 3 shows a graph of the results of the energy density against the space ratio for the lithium - ion secondary battery of Example 1. Here, the space ratio is the ratio of the total volume of the pores to the porosity of the negative electrode current collector.

[0072]

Table 1

[0073] As shown in Table 1, the lithium - ion secondary batteries of Examples 1 - 5 all showed high energy density values exceeding 800 Wh / L. For the lithium - ion secondary battery of Comparative Example 1, although the value of the energy density was high, unstable Li precipitation occurred during charging, resulting in abnormal charging and micro short - circuit, and stable charge - discharge could not be carried out. Therefore, the secondary battery of Comparative Example 1 may cause internal short - circuit and the like. The lithium - ion secondary battery of Comparative Example 2 had a lower energy density compared to Examples 1 - 5. For the lithium - ion secondary battery of Comparative Example 3, the electrode ruptured during the charge - discharge test (the energy density could not be measured).

[0074] 3, the energy density tends to decrease when the ratio of the total volume of the holes to the porosity exceeds 8%, and tends to decrease significantly when the ratio exceeds 10%. From this, it is considered that a high energy density can be easily maintained stably when the ratio of the total volume of the holes to the porosity is 8% or less. [Explanation of symbols]

[0075] 1 negative electrode 21 Negative electrode current collector 22 Hole 23 Negative electrode active material 31 Solid electrolyte W Thickness direction R (hole) diameter H (hole) depth

Claims

1. A negative electrode of a solid-state battery, The negative electrode current collector is made of a metal porous body, and a negative electrode active material is filled in the negative electrode current collector. the negative electrode current collector is provided with a hole portion having no metal porous body in a thickness direction from a surface on a solid electrolyte side, The pores have a pore diameter of 100 μm to 180 μm.

2. 2. The negative electrode for a solid-state battery according to claim 1, wherein a ratio of a total volume of the pores to a porosity of the metal porous body (total pore volume / porosity) is 10 vol% or less.

3. 2. The negative electrode for a solid-state battery according to claim 1, wherein a ratio of a total volume of the pores to a porosity of the metal porous body (total pore volume / porosity) is 8 vol% or less.

4. The negative electrode for a solid-state battery according to claim 1 , wherein the pores have a depth in the thickness direction of 3 μm or more.

5. The negative electrode of the solid-state battery according to claim 1 , wherein the pores have a depth in the thickness direction of 5 μm or more.

6. The negative electrode of the solid-state battery according to claim 1 , wherein the hole is a through hole.

7. The negative electrode of the solid-state battery according to claim 1 , wherein the hole has a cross-sectional shape of a circle or a square.

8. The negative electrode of the solid-state battery according to claim 1 , wherein the negative electrode active material is a silicon-based material.

9. A solid-state battery comprising the negative electrode according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Negative electrode and negative electrode complex of lithium air battery, and lithium air battery

    JP2016009522A

  • Lithium metal secondary battery

    JP2018206757A

  • Three-dimensional porous aluminum mesh for use in collector, and electrode, nonaqueous-electrolyte battery, capacitor, and lithium-ion capacitor using said porous aluminum

    WO2012111659A1

  • Lithium ion secondary battery

    WO2014128844A1

  • Electrode for lithium ion secondary battery and lithium ion secondary battery

    JP7008737B2